Tiny stitches : the life of medical pioneer Vivien Thomas - Hooks, Gwendolyn (Lee & Low Books Inc., 2016)
"Biography of Vivien Thomas, an African-American surgical technician who pioneered the procedure used to treat babies with a heart defect known as 'blue baby syndrome.' Includes author's note and author's sources"--